Insidad Bab al-Ijtihad dan Pengaruhnya Terhadap Madhhab Shafi’i - Luthfi Hadi Aminuddin (Justicia Islamica, 2012)
This work is based on historcal Islamic legal development especially discourse of closing ijtihad ’authority’. Moslem and non-moslem specialist writers sure that this discourse happened pasca a’immat al-madhahib phase.  This phase refers to the era when the creative thinking is stagnant. Amount of Shafi’ithe ulama> who state a binding ruling in religious matters of closing ijtihad authority, according to them, are responsible. This paper is to show that closing ijtiha>d ’authority’ discourse (insidad bab al-ijtihad) begins from the times when al-Ghaza>li>, al-Ra>fi’i>, and al-Nawa>wi> clasify mujtahid prerequsites. Their ’mujtahid qualifications’ are efforts which can close ijtiha>d ’authority’ (bab> al-ijtiha>d). Mujtahids did do Ijtiha>d as a creative thinking such as insha>’i> and intiqa>’i>. But they did this as mujtahid muntasib, mujtahid fi> al-madhhab or al-mujtahid al-murajjih} as a different level from mujtahid mustaqill. As}ha>b al-Sha>fi”˜i> such as al-Muzani>, al-Buwayt}i>, a-Juwayni>, al-Shayra>zi>, al-Ghaza>li>, al-Ra>fi”˜i> and al-Nawa>wi> standardize istinba>t} method which Sha>fi’i> formulated.